2018
DOI: 10.1089/chi.2018.0019
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Obesity Declines Project: A Different Methodology

Abstract: Background: The evidence for and our understanding of community-level strategies such as policies, system, and environmental changes that support healthy eating and active living is growing. However, researchers and evaluation scientists alike are still not confident in what to recommend for preventing or sustaining declines in the prevalence of obesity.Methods: The Systematic Screening and Assessment (SSA) methodology was adapted as a retrospective process to confirm obesity declines and to better understand … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Other studies have described associations between ECE policies and child outcomes using retrospective methods, but these too are unable to assess changes over time. For example, in 2018, researchers evaluated correlations between local-and state-level childhood healthy eating and physical activity policies and obesity rates [74] and found that the 4 pre-selected study locations with declining childhood obesity rates had contemporaneously enacted relevant policies [75]. This scoping retrospective described general relationships between the policy environment and childhood obesity, but could not, as the authors noted, elucidate causal pathways [75].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have described associations between ECE policies and child outcomes using retrospective methods, but these too are unable to assess changes over time. For example, in 2018, researchers evaluated correlations between local-and state-level childhood healthy eating and physical activity policies and obesity rates [74] and found that the 4 pre-selected study locations with declining childhood obesity rates had contemporaneously enacted relevant policies [75]. This scoping retrospective described general relationships between the policy environment and childhood obesity, but could not, as the authors noted, elucidate causal pathways [75].…”
Section: Discussionmentioning
confidence: 99%